The Benchmarking management guide - American Productivity and Quality Center (Oregon : Productivity Press, 1993)
The new benchmarking management guide by the American Productivity and Quality Center offers valuable signposts to help practitioners avoid many of the potential pitfalls in benchmarking.
Getting started in benchmarking -- Conducting a benchmarking study -- Building a benchmarking organization
Keywords: BENCHMARKING (MANAGEMENT)